Role of N-Nitro-L-Arginine-Methylester as anti-oxidant in transient cerebral ischemia and reperfusion in rats - Awooda, Hiba A (BioMed Central, 2013)
BACKGROUND: Previous reports assessing the neuroprotective role of nonselective Nitric Oxide synthase (NOS) inhibitor N-nitro-L-arginine-methylester (L-NAME) following cerebral ischemia/reperfusion are contradictory. The aim of this work was to examine the potential benefits of L-NAME on rats subjected to transient focal cerebral ischemia/reperfusion. METHODS: The study involved 30 adult male Wistar rats divided into three groups 10 rats in each: First group was sham-operated and served as a control, a ischemia/reperfusion (I/R) group of rats infused with 0.9% normal saline intraperitoneally 15 minutes prior to 30 minutes of left common carotid artery (CCA) occlusion and a test group infused with L-NAME intraperitoneally 15 minutes prior to ischemia. Neurobehavioral assessments were evaluated and quantitative assessment of malondialdehyde (MDA), Nitric oxide (NO) metabolites and total antioxidant capacity (TAC) in both serum and the affected cerebral hemisphere were achieved. RESULTS: Rats’ neurological deficit and TAC were significantly decreased while NO and MDA were significantly increased in the I/R compared with the control group (P < 0.001). Alternatively in the L-NAME group, neurological deficit and TAC were significantly improved while NO and MDA were significantly decreased compared to I/R group (P < 0.001). CONCLUSIONS: L-NAME pretreatment for rats undergoing cerebral ischemia/reperfusion significantly improves neurological deficit while reducing oxidative stress biomarkers in the affected cerebral hemisphere.